PERAN BIMBINGAN KONSELING ISLAM DALAM MENINGKATKAN KEMAMPUAN INTERAKSI SOSIAL ANAK AUTISME MELALUI PROGRAM PAGI CERIA DAN KEGIATAN OUTDOOR DI SEKOLAH KHUSUS AUTISME BINA ANGGITA YOGYAKARTA - Henny, Henny; Sa'adah, Nurus (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to examine the role of Islamic counseling in improving the social interaction skills of children with autism through the Morning Ceria program and outdoor activities at the Bina Anggita Autism Special School, Yogyakarta. The focus of this research is how a combination of Islamic counseling principles and structured outdoor activities can support the social development of children diagnosed with Autism Spectrum Disorder (ASD). Using a qualitative approach, this case study involved interviews, observations, and document analysis to collect data from teachers, counselors, and students at the school. Research findings show that the Morning Ceria program and outdoor activities significantly increase students' ability to interact with peers and the surrounding environment. The application of Islamic counseling guidance, which integrates spiritual and emotional support, provides a comprehensive framework in supporting the development of social interaction skills for children with autism. The conclusions of this study suggest that Islamic counseling can be an effective strategy in educational settings to help children with autism improve their social interactions. This research also opens up opportunities for further studies regarding the long-term impact of this intervention in a broader educational context.